(untitled) (Bangladesh Journal of Agricultural Research, 2017)
Genetic diversity study was done in 64 maize inbreds grown under excess soil moisture condition.The genotypes were grouped into eight clusters. It was observed that all intercluster distances were larger than all intracluster distances. Such results indicated that genotypes included within a cluster had less diversity among themselves but wider genetic diversity among the inbreds of different clusters. The highest inter cluster distance was observed between cluster IV & VII followed by IV & V , IV & VIII, II & VII and I & IV. The highest intra cluster distance was noticed in cluster V and the lowest was in cluster VII. The highest yield/plant, cob girth, number of rows/ear, number of grains/plant, SPAD value and number of nodes with brace roots were observed in cluster IV. The lowest mean value for yield/plant yield components and dwarf statured plant were observed in cluster VII. The plant height, ear height,days to 50% tasseling and silking, cob length, cob girth, 100 grain weight and SPAD value contributed considerably to total divergence. The genetically diverged genotypes in these distinct clusters could be used as parents in hybridization program for getting desirable hybrid(s). Bangladesh J. Agril. Res. 42(2): 379-385, June 2017